Common mental disorders are not diagnosed commonly in community health centres - Tsepo S. Motsohi; A. A. Isaacs; N. Manga; C. Le Grange; M. Roelofse; P. Milligan; D. A. Hellenberg; A. R. Sayed (South African Family Practice)
Background: Very limited published data exist on the spectrum of mental health disorders encountered at primary health care (PHC) facilities in South Africa.